Neonatal mortality of pigs in Nsukka, Southeast Nigeria - Abonyi, F. O.1; Omeh C.V.O; Machebe, N. S.2 (African Journal of Pig Farming, 2019)
This study was conducted to investigate the causes of neonatal mortality among pig farms in Nsukka Local Government area of Enugu State, Nigeria. Forty (40) pig farms in the study area were randomly selected and used for the 20 weeks study duration. One week post partum was considered as the neonatal period. A total of 124 pregnant sows and 924 piglets farrowed during the study period were used. Data were obtained from farm visitations/physical observations, farm records, oral interviews and structured questionnaires. Feed samples were analyzed for their proximate contents. Pregnant pigs were weighed prior, during and few days after farrowing, while piglets were weighed within seven days after farrowing. Necropsy and bacteriological examinations of samples of feed, maternal and diseased or dying neonates were also carried out. Results showed that mean litter size, piglet weight at birth and daily weight gain were 7.45 ± 0.02, 1.01 ± 0.03 and 0.21 ± 0.01 kg, respectively. 164 (17.75%) of total piglets farrowed died within the first week of life (neonatal period), whereas 144 (87.80%) of this number died within the first five days. In addition, 48 (29.27%) were over laid, 30 (18.29%) died of scouring caused by Escherichia coli and Salmonella organisms, 30 (18.29%) died of hypoglycaemia. On the other hand, 20 (12.20%) piglets were cannibalized by older pigs and or their dams, 16 (9.75%) were trapped within the drainage, 12 piglets (7.32%) died of chilling, while eight (4.88%) died of unknown causes. Other contributory factors include inappropriate farm structures, absence or inadequate farm records, nutritional imbalance, improper management practices and inadequate veterinary services. It was concluded that neonatal mortality is a major impediment to optimum profit making from swine enterprise in Nsukka, South Eastern Nigeria.